METHODOLOGY FOR DEVELOPING INDEPENDENT LEARNING ACTIVITY IN PRIMARY SCHOOL STUDENTS BASED ON STEAM TECHNOLOGY - Madina Turdiyeva (Research Focus International Scientific Journal, 2024)
This study investigates the impact of STEAM (Science, Technology, Engineering, Arts, and Mathematics) education on independent learning activity among primary school students. Using a mixed-methods approach, 60 students were divided into an experimental group that received STEAM-based instruction and a control group that followed the traditional curriculum. Over an eight-week period, the experimental group engaged in interdisciplinary, hands-on activities designed to foster critical thinking, creativity, and autonomy in learning. Results from pre- and post-assessments revealed that the experimental group showed significant improvements in critical thinking and independent learning behaviors compared to the control group. This study contributes to educational practices by highlighting the benefits and feasibility of integrating STEAM methodologies in primary education.